The overexpression of cyclin D1 is a positive prognostic factor in advanced-stage breast carcinoma cases - Aksoy, Asude; Sevim, Merve; Artas, Gokhan (Kare Publ, 2023)
OBJECTIVE: Cyclin D1 (CDDN1) is a protein required for mitotic cell cycle progression through the G1 phase, as well as a regulatory component of the cyclin-dependent kinases CDK4 and CDK6. In this study, we wanted to evaluate the relationship between CDDN1 expression and clinicopathological features in breast cancer (BC) cases and whether CDDN1 could be used as a prognostic biomarker for BC cases. METHODS: A total of 70 cases, 30 cases each with limited and advanced-stage BC, and as the control group, 10 healthy breast tissue, without a cancer diagnosis, with examined for benign reasons (mammoplasty, breast reduction surgery, etc.) were included in this study. The pathological specimens from the cases were stained, immunohistochemically, and categorized as a low (L) group or a high (H) group for CDDN1 expression. The cases' clinicopathological features and survival rates were evaluated statistically, within a 95% of confidence interval, p<0.05, retrospectively. RESULTS: The median follow-up period of the cases was 48.00 (range, 6-150) months. CDDN1 expression was significantly higher in advanced-stage BC cases than in normal breast tissue and limited-stage BC cases. The median overall survival (OS) was 96 months (CI 95%: 67.74-117.59) in the H-CDDN1 group, compared to the L-CDDN1 group not reached, but there was no relation (p>0.05). CDDN1 overexpression was more prominent in low-grade advanced BC cases (p=0.004). The median OS of advanced-stage BC cases with Grade 1 was significantly longer than those with other grades (p=0.04). CONCLUSION: Our results suggest that CDDN1 expression can be used as a potentially appropriate positive prognostic biomarker for advanced-stage BC cases.
Keywords: Biomarker; breast carcinoma; cyclin D1; prognosis